Sun-Dried Bilimbi (Averrhoa Bilimbi L) as an Additional Income For Housewives In Ujong Tanoh Darat Village, Meureubo Sub-District, Aceh Barat Regency, Aceh - Rusdi Faizin; Raidayani Raidayani; Yoga Nugroho; Irma Yanti (Budapest International Research and Critics University, 2020)
This study aims to calculate the additional amount of housewife income in Ujong Tanoh Darat Village, Meureubo District, West Aceh Regency as a producer of sun-dried bilimbi. Respondents in this study were ten producers in Ujong Tanoh Darat Village. Data collection techniques by observing and interviewing in detail related to the analysis of sun-dried bilimbi producer income. The data analysis method uses cost analysis, production revenue, production income, and revenue cost ratio (R / C). From the results of data processing in this study, it found that the average income earned by producers was Rp.300,550 per cycle, the average producer income was Rp. 602,000 per cycle and the average production cost incurred by producers is Rp.301,499 per cycle, and the R per C ratio obtained is 1.9, greater than 1 meaning the sun-dried bilimbi producer business in Ujong Tanoh Darat Village, Meureubo District West Aceh is feasible.